2020
DOI: 10.3168/jdsc.2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Regrouping induces anhedonia-like responses in dairy heifers

Abstract: Regrouping (i.e., mixing individuals to form a new social group) is common on dairy farms. The practice is known to be stressful, but how cattle react emotionally to this stressor is still poorly understood. We studied whether heifers experience anhedonia (i.e., the reduced ability to experience pleasure) following regrouping by comparing their use of a mechanical brush before and after regrouping. Heifers reduced their use of the brush 8 h after regrouping, suggesting that they were experiencing anhedonia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
3
6
1
Order By: Relevance
“…Experiment 1 did not aim at disentangling which specific stressors were affecting cows. In contrast with previous results showing a reduction in brush use only on the day of social mixing [ 10 ], the current study also found that cows changed their brush use for weeks following parturition. This suggests that post-partum stressors may in fact induce more severe welfare issues than those observed after social mixing alone.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Experiment 1 did not aim at disentangling which specific stressors were affecting cows. In contrast with previous results showing a reduction in brush use only on the day of social mixing [ 10 ], the current study also found that cows changed their brush use for weeks following parturition. This suggests that post-partum stressors may in fact induce more severe welfare issues than those observed after social mixing alone.…”
Section: Discussioncontrasting
confidence: 99%
“…One limitation of our study is that brush use was not consistent prepartum; the progressive decrease in latency and increase in brush use over the four-week period suggests that cows were still learning to use the brush and getting used to the testing routine. This result is consistent with previous reports, indicating that cows need time to master the use of the brush [ 22 ], and need many pre-testing sessions to obtain consistent measures when the brush is provided for limited periods [ 10 ]. One challenge in the current study is that cows were tested alone, and this may increase the time required to learn to use the brush effectively (most animals used it on the head and the neck before discovering it could be used on the back).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…nonfood rewards) may allow stronger inferences. For instance, we recently found that weaned calves reduce their use of a mechanical brush after social mixing [39].…”
Section: Plos Onementioning
confidence: 99%